Analisis Pengetahuan Kesehatan Reproduksi Asupan Zat Gizi Dengan Status Gizi Pada Remaja Putri - Fitriani, Fitriani; Julianawati, Tinta; Sibarani, Indah Nurcahaya (Bunda Edu-Midwifery Journal (BEMJ), 2024)
One of the causes of the problem of adolescent nutritional status in Indonesia is a practice problem or action that is affected by a lack of nutritional knowledge. This research aims to analyze the influence of socialization on increasing knowledge and attitudes about reproductive health nutrition among adolescents at SMAN 20 Batam City. This research uses a quasi-experimental method. The design used is one group pre-test and post-test design. The population in this study were teenagers at SMAN 20 Batam City. The sample was taken by purposive sampling as many as 45 teenagers. This research was carried out in May 2024 over a period of 10 days. Statistically analyzed using the Spearman Rank Correlation test. The test results produce a significance value of p value 0.000 <